2017
DOI: 10.1155/2017/3572365
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Parameter Identification of Fractional‐Order Duffing System Based on Differential Evolution Algorithm

Abstract: Using the dynamic properties of fractional-order Duffing system, a sequential parameter identification method based on differential evolution optimization algorithm is proposed for the fractional-order Duffing system. Due to the step by step parameter identification method, the dimension of parameter identification of each step is greatly reduced and the search capability of the differential evolution algorithm has been greatly improved. The simulation results show that the proposed method has higher convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To estimate the orders and parameters in an incommensurate fractional-order chaotic system, Zhu et al [95] proposed a switching differential evolution scheme, where the switching population size is adjusted dynamically. Motivated by this proposal, Lai et al [96] employed a sequential parameter identification method for a fractional-order Duffing system based on a differential evolution scheme. These authors then demonstrated an improved convergence of the proposed algorithm via numerical implementation.…”
Section: System Identificationmentioning
confidence: 99%
“…To estimate the orders and parameters in an incommensurate fractional-order chaotic system, Zhu et al [95] proposed a switching differential evolution scheme, where the switching population size is adjusted dynamically. Motivated by this proposal, Lai et al [96] employed a sequential parameter identification method for a fractional-order Duffing system based on a differential evolution scheme. These authors then demonstrated an improved convergence of the proposed algorithm via numerical implementation.…”
Section: System Identificationmentioning
confidence: 99%
“…Nguyen et al [6] investigated the subharmonic resonance of a Duffing oscillator with a fractional-order derivative and analyzed its stability. In reference [7,8], the fractional-order Duffing system was investigated by a numerical method. The bifurcation behavior of a fractional-order Duffing system was studied, and its rich nonlinear behavior was found [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The modified quantum bacterial foraging algorithm is applied to identify the parameters of the fractional-order system, which has a faster convergence rate and higher accuracy [27]. Literature [28][29][30] proposed improved differential (DE) evolution (IDE) algorithm, respectively, and applied to identify fractional-order chaotic system parameters, which greatly improves the identification speed and accuracy.…”
Section: Introductionmentioning
confidence: 99%